Clement Comer Clay, Digest of the Laws of Alabama 416, § 31 (1843) - (:unkn) unknown (My University, 1843)
Prohibited assault and battery of another with a cowhide, stick, or whip while in possession of a pistol or other deadly weapon with the intent to intimidate another to prevent the person from defending himself. Violators imprisoned not less than two nor more than twenty years.
Keywords: CARRY - INTENT TO COMMIT CRIME